KONSTRUKSI HUKUM ACARA PERDATA DALAM MENYELESAIKAN EKSEPSI MATERIIL: UPAYA MENGELIMINASI INEFISIENSI PUTUSAN NIET ONTVANKELIJKE VERKLAARD (NO) BERDASARKAN PASAL 136 HIR - Muhamad Febin; Danil Wirawan; Risnauli Simanjuntak; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
This study examines the inconsistency in the application of Article 136 HIR/162 RBg in Indonesian civil procedural law practice, particularly regarding judicial treatment of material exceptions (eksepsi materiil) that result in Niet Ontvankelijke Verklaard (NO) rulings. The legal ideal enshrined in Article 2(4) of Law Number 48 of 2009 on Judicial Power requires proceedings to be simple, fast, and inexpensive. In practice, however, cases that have undergone dozens of evidentiary hearings still conclude with NO rulings on grounds of formal defects in the claim, causing significant temporal and financial harm to justice seekers. This research employs a normative juridical method with statutory, conceptual, and legal-historical approaches. The findings reveal that the root cause lies in the regulatory nature of Article 136 HIR, which carries no sanction, thereby generating divergent judicial interpretations. A further evaluation demonstrates that prevailing practice substantially contradicts the principle of simple, swift, and affordable adjudication. The strategic recommendation of this study is the urgent formulation of standardized parameters through a Supreme Court Regulation (Perma) or a Supreme Court Circular (SEMA).